2012
DOI: 10.3109/13685538.2012.716877
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in male patients with osteoporosis: results of a cross sectional study

Abstract: This analysis confirms the association between number of fractures and worse estimation of HRQoL in male patients. Because men are 3 times less likely to suffer from osteoporosis than women, the specific HRQoL characteristics of male patients with this disease can often be overlooked. Clinicians should consider mental health referral especially for osteoporotic male patients having experienced ≥2 fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Osteoporosis can lead to multiple adverse consequences, including chronic pain, fragility fractures, sarcopenia, physical disability, which may impair the quality of life of the patients [ 28 , 29 ]. We evaluated the HRQoL of Chinese men with primary osteoporosis or osteopenia in detail for the first time, and confirmed that the poorer quality of life in osteoporotic men than healthy controls, especially in the physical function domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis can lead to multiple adverse consequences, including chronic pain, fragility fractures, sarcopenia, physical disability, which may impair the quality of life of the patients [ 28 , 29 ]. We evaluated the HRQoL of Chinese men with primary osteoporosis or osteopenia in detail for the first time, and confirmed that the poorer quality of life in osteoporotic men than healthy controls, especially in the physical function domain.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analysis studies demonstrated that HRQoL of men with osteoporosis was impaired more obviously in physical function than mental function, which were consistent with our results [ 12 , 14 , 30 ]. Through EQ-5D questionnaire, another study found that pain/discomfort and anxiety/depression were common in men with osteoporosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that patients diagnosed with vertebral fractures might benefit from case finding for mood disorders, such as depression, a risk factor for suicide, and enquiring about suicide and self-harm. 40 Osteoporosis is commonly diagnosed and patients seek help for fracture care in primary care, which may therefore be an important setting to identify patients at risk of self-harm and suicide and intervene early. New research would enable the assessment of the feasibility, acceptability, and effectiveness of such approaches.…”
Section: Discussionmentioning
confidence: 99%